Differing Alterations of Two Esca Associated Fungi, Phaeoacremonium aleophilum and Phaeomoniella chlamydospora on Transcriptomic Level, to Co-Cultured Vitis vinifera L. calli. - Jochen Fischer; Stéphane Compant; Romain J G Pierron; Markus Gorfer; Alban Jacques; Eckhard Thines; Harald Berger (PLoS ONE, 2016)
The filamentous fungi Phaeoacremonium aleophilum (P.al, Teleomorph: Togninia minima) and Phaeomoniella chlamydospora (P.ch) are believed to be causal agents of wood symptoms associated with the Esca associated young vine decline. The occurrence of these diseases is dramatically increasing in vineyards all over the world whereas efficient therapeutic strategies are lacking. Both fungi occupy the same ecological niche within the grapevine trunk. We found them predominantly within the xylem vessels and surrounding cell walls which raises the question whether the transcriptional response towards plant cell secreted metabolites is comparable. In order to address this question we co-inoculated grapevine callus culture cells with the respective fungi and analyzed their transcriptomes by RNA sequencing. This experimental setup appears suitable since we aimed to investigate the effects caused by the plant thereby excluding all effects caused by other microorganisms omnipresent in planta and nutrient depletion. Bioinformatics analysis of the sequencing data revealed that 837 homologous genes were found to have comparable expression pattern whereas none of which was found to be differentially expressed in both strains upon exposure to the plant cells. Despite the fact that both fungi induced the transcription of oxido- reductases, likely to cope with reactive oxygen species produced by plant cells, the transcriptomics response of both fungi compared to each other is rather different in other domains. Within the transcriptome of P.ch beside increased transcript levels for oxido- reductases, plant cell wall degrading enzymes and detoxifying enzymes were found. On the other hand in P.al the transcription of some oxido- reductases was increased whereas others appeared to be repressed. In this fungus the confrontation to plant cells results in higher transcript levels of heat shock and chaperon-like proteins as well as genes encoding proteins involved in primary metabolism.